Synthesis, Optimization and Characterization of Metallic Ion and Levofloxacin Loaded Nanomaterials-Based Therapeutics against Multidrug-Resistant Pseudomonas aeruginosa - Rashmi, Rashmi; Sethi, Neeraj (Journal of Neonatal Surgery, 2025)
The rise of multidrug-resistant (MDR) Pseudomonas aeruginosa poses a significant challenge in clinical settings, necessitating novel antimicrobial strategies. This study reports the synthesis, optimization, and characterization of zinc nanoparticles (ZnNPs) co-loaded with levofloxacin to enhance antibacterial efficacy. Zinc nanoparticles were synthesized via a chemical precipitation method and optimized at pH 8.0, with a zinc acetate concentration of 0.1 M, yielding particles with an average size of 80 ± 5 nm and a drug loading efficiency of 74.5%. Characterization by UV-Vis, FTIR, XRD, DLS, SEM, and TEM confirmed successful synthesis and drug incorporation. The nanoparticles exhibited a zeta potential of -25 mV, indicating good colloidal stability. In-vitro studies against MDR P. aeruginosa revealed that Zn-Levofloxacin nanoparticles achieved a minimum inhibitory concentration (MIC) of 2 µg/mL, compared to 8 µg/mL for levofloxacin alone. Disk diffusion assays showed an inhibition zone of 30 ± 2 mm for the nanoparticle formulation versus 20 ± 1.5 mm for the free drug. Time-kill assays demonstrated >99.9% bacterial reduction within 6 hours. These results suggest that zinc-levofloxacin nanocomposites offer a promising and potent therapeutic alternative against MDR P. aeruginosa.